Membangun Ketahanan Demokrasi: Peran Pendidikan Politik dalam Mendorong Keterlibatan Pemilih - Irawan, Anang Dony; Yustitianingtyas, Levina; Setiawan, Bahri Nur (Media of Law and Sharia, 2025)
The importance of political education lies in the principle of popular sovereignty, which holds that a just government is determined by the people and must be held accountable to them. Limited public exposure to political education has led to immature participation and weak attitudes toward the democratic process. Left unaddressed, this may trigger conflicts, undermine security, and risk national disintegration. This research aims to assess the extent to which political education can be regarded as a planned and structured process designed to shape voters’ political identity, foster political awareness, and cultivate ethically and morally responsible participation. Political education, as a product of public policy, can be evaluated directly during its implementation. It serves as a step toward achieving policy objectives through administrative and political measures. Using a normative juridical legal research method with a statutory approach, this study examines the internal aspects of positive law related to political education. Findings indicate that voter participation remains minimal despite its vital role in sustaining democracy. Active and informed voter engagement is essential for building a strong and lasting democratic foundation. The study highlights that political education should be a continuous process within communities, not limited to the period preceding elections. This is particularly relevant in the context of Indonesia’s upcoming 2029 General Elections and 2029 Simultaneous Regional Elections, where the focus should shift from short-term mobilisation to long-term democratic capacity building